การพัฒนาเทคนิคเชิงสร้างสรรค์เพื่อเสริมสร้างสัมพันธภาพเชิงบวก ในการให้คำปรึกษากลุ่มวัยรุ่น - วรเจริญศรี, สกล (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) ศึกษาองค์ประกอบสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่น 2) พัฒนาเทคนิคเชิงสร้างสรรค์เพื่อเสริมสร้างสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่น และ 3) ศึกษาผลการใช้เทคนิคเชิงสร้างสรรค์เพื่อเสริมสร้างสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่น โดยแบ่งการศึกษาออกเป็น 2 ระยะ คือ ระยะที่ 1 การศึกษาองค์ประกอบสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่น ผู้วิจัยเก็บข้อมูลจากประชากรทั้งหมด เป็นการเก็บรวบรวมข้อมูลจากนิสิตระดับปริญญาตรีชั้นปีที่ 2 หลักสูตรการศึกษาบัณฑิต มหาวิทยาลัยศรีนครินทรวิโรฒ ปีการศึกษา 2559 จำนวน 412 คน และระยะที่ 2 การศึกษาผลการใช้เทคนิคเชิงสร้างสรรค์เพื่อเสริมสร้างสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่น มีกลุ่มตัวอย่างทั้งสิ้น จำนวน 54 คน ซึ่งได้มาโดยวิธีการเลือกแบบเจาะจง และแบ่งออกเป็น 2 กลุ่ม โดยพิจารณาจากผลการศึกษาในระยะที่ 1 คัดเลือกนิสิตที่มีคะแนนสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มตั้งแต่เปอร์เซ็นไทล์ที่ 33 ลงมา และมีความสมัครใจเข้าร่วมการทดลอง การสุ่มตัวอย่างเข้าสู่กลุ่มทดลองและกลุ่มควบคุม โดยกลุ่มทดลองแบ่งออกเป็น 8 กลุ่ม และกลุ่มควบคุม 1 กลุ่ม แต่ละกลุ่มมีจำนวนสมาชิกกลุ่มละ 6 คน เครื่องมือที่ใช้ในการวิจัย คือ แบบสัมภาษณ์กึ่งมีโครงสร้าง แบบสอบถามและแบบสังเกตพฤติกรรมสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่น เทคนิคเชิงสร้างสรรค์ 8 เทคนิคและแบบรายงานตนเอง วิเคราะห์ข้อมูลโดยใช้การวิเคราะห์เชิงเนื้อหาสำหรับข้อมูลเชิงคุณภาพ และใช้เทคนิคการวิเคราะห์องค์ประกอบเชิงยืนยัน การเปรียบเทียบความแตกต่างระหว่างค่าเฉลี่ยด้วยสถิติ t-test for Dependent และ t-test for Independent ผลการวิจัยสรุปได้ดังนี้ 1. โมเดลการวัดสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่นที่ผู้วิจัยสร้างขึ้นตามแนวคิดของไคลน์ คอเรย์และคอเรย์ ประกอบด้วย 7 องค์ประกอบ ได้แก่ ความใส่ใจ ความร่วมมือ การเปิดเผยตนเอง การสนับสนุนในกลุ่ม ความรู้สึกสบายใจและไว้วางใจ การแสดงความคิดและความรู้สึก และการยอมรับสมาชิก มีค่าความสอดคล้องกลมกลืนกับข้อมูลเชิงประจักษ์ ( =330.29 df=292 p=.06 GFI=0.95 AGFI=0.92 CFI=1.00 RMSEA=0.01 SRMR=0.04) มีน้ำหนักองค์ประกอบมาตรฐานอยู่ในเกณฑ์สูงมีค่าระหว่าง 0.56 – 0.94 มีนัยสำคัญทางสถิติที่ระดับ .01 2. เทคนิคเชิงสร้างสรรค์เพื่อเสริมสร้างสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่นที่ผู้วิจัยพัฒนาขึ้น มี 8 เทคนิค ได้แก่ เทคนิคบอลพิศวง เทคนิคศิลปะของฉัน เทคนิคนิตยสารของฉัน เทคนิคอัลบั้มเพลงชีวิต เทคนิคกวีชีวิตข้อคิดคำคม เทคนิคคำพยากรณ์ เทคนิคเกมกระดานบอกเล่าเก้าสิบ และเทคนิคสิ่งแทนฉัน ประกอบด้วยขั้นตอนการดำเนินการ 3 ขั้นตอน คือ ขั้นนำ ขั้นดำเนินการและขั้นสรุป ตลอดจนใช้แนวคิดการเรียนรู้ผ่านการได้รับประสบการณ์ และการเรียนรู้ผ่านการสอนในการดำเนินการให้คำปรึกษากลุ่ม 2 3. กลุ่มทดลองทั้ง 8 กลุ่มที่ได้รับเทคนิคเชิงสร้างสรรค์มีสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่นหลังการทดลองสูงกว่าก่อนการทดลอง อย่างมีนัยสำคัญทางสถิติที่ระดับ .01 แสดงว่าเทคนิคเชิงสร้างสรรค์แต่ละเทคนิคมีผลทำให้สัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่นเพิ่มขึ้น 4. กลุ่มทดลองทั้ง 8 กลุ่มที่ได้รับเทคนิคเชิงสร้างสรรค์มีสัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่นสูงกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 โดยกลุ่มทดลองที่ได้รับเทคนิคเกมกระดานบอกเล่าเก้าสิบมีความแตกต่างของค่าเฉลี่ยสูงที่สุด และรองลงมาคือ เทคนิคบอลพิศวง เทคนิคอัลบั้มเพลงชีวิต เทคนิคกวีชีวิตข้อคิดคำคม เทคนิคคำพยากรณ์ เทคนิคศิลปะของฉัน เทคนิคสิ่งแทนฉัน และเทคนิคนิตยสาร ของฉัน ตามลำดับ คำสำคัญ: เทคนิคเชิงสร้างสรรค์ สัมพันธภาพเชิงบวกในการให้คำปรึกษากลุ่มวัยรุ่น Abstract The purposes of this research were 1) to study the components of positive relationship in adolescents’ group counseling; 2) to develop creative techniques for enhancing positive relationships in adolescents’ group counseling and 3) to study the effect of using creative techniques for enhancing positive relationships in adolescents’ group counseling. The study was conducted in two phases: Phase I: To study the components of the positive relationship in adolescents’ group counseling, the target population was specified among 412 second year undergraduate students in Education, Srinakharinwirot University, Academic Year 2016. Phase II : Regarding investigating the effects of using creative techniques to enhance positive relationship in adolescent’s group counseling, 54 samples, selected by the purposive sampling methods, were divided into two groups. These samples were also considered by the results from Phase I, in which their scores of positive relationship in adolescents’ group counseling were lower than 33rd percentile, and with their voluntary participation in the experiment. There were one control group and eight experimental groups, comprising six members in each one. The research instruments were semi-structure interview form, positive relationship in adolescents’ group counseling questionnaire, a behavioral observation checklist, eight creative techniques and self-report form. Content analysis for qualitative data and confirmatory factor analysis technique were used to analyze the data. Furthermore, to compare the difference of mean scores, t-test (for dependent and independent samples) was employed in this study. The research results were as follows: 1. The model of measurement of positive relationships in adolescents’ group counseling was based on the concepts of Kline, Corey and Corey, which were characterized into seven components: attention, cooperation, self-disclosure, support of group members, feeling of comfort and trust, expressing of thoughts and feeling, and group members’ acceptance. These seven components were inaccordance with empirical data ( =330 .29 df=292 p=.06 GFI=0.95 AGFI=0.92 CFI=1.00 RMSEA=0.01 SRMR=0.04), with the high loading factor ranging from 0.56 – 0.94 at significant level of .01. 2. Eight creative techniques, developed by the researcher, for enhancing positive relationships in adolescents’ group counseling were amazing ball, my art, my magazine, my life music album, poetic life quotes, horoscopes, 90 storytelling board game, and self-representation. Each technique consisted of three phases: beginning, working and ending, and using experiential and didactic learning in group counseling. 3. After the experiment, all of the eight experimental groups, which received creative techniques with positive relationship in group counseling, scored higher than before the experiment, with a statistically significant difference at the level of .01. Each of the techniques was also found to be capable of enhancing positive relationships in group counseling among adolescents. 4. The scores of eight experimental groups received creative techniques with positive relationship in adolescents’ group counseling rated higher than the control group with a statictically significant difference at the level of .01. The results also revealed that the experimental groups which received the technique of a storytelling board game had the highest difference in means. Futhermore, the sores ranked lower in mean difference were found in the techniques of an amazing ball, my life music album, poetic life quotes, horoscopes, my art, self-representation and my magazine, respectively. Keywords : Creative Techniques, Positive Relationships in Adolescents’ Group Counseling